2021
DOI: 10.1097/cin.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Data, Information, and Knowledge in the Nursing Handoff

Abstract: Miscommunication occurring during the nursing handoff continues to be a primary cause of sentinel events and adverse patient outcomes. The primary purpose of the nursing handoff is to communicate essential patient data, information, and knowledge to ensure the safe continued continuity of care. The aim of this study was to examine the content of the nurse-to-nurse change-of-shift handoff communication in terms of data, information, and knowledge for both bedside and nonbedside handoffs of a patient who has exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Our study was organized following the framework of the Nurse‐to‐Nurse Transition of Care Communication Model (Galatzan & Carrington, 2022). This framework provides a mechanism and structure to examine the nurse‐to‐nurse handoff communication at any point when a patient transitions care from one provider to another.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study was organized following the framework of the Nurse‐to‐Nurse Transition of Care Communication Model (Galatzan & Carrington, 2022). This framework provides a mechanism and structure to examine the nurse‐to‐nurse handoff communication at any point when a patient transitions care from one provider to another.…”
Section: Methodsmentioning
confidence: 99%
“…This framework provides a mechanism and structure to examine the nurse‐to‐nurse handoff communication at any point when a patient transitions care from one provider to another. Within this model, the analysis of handoff communication encompasses an exploration of structural elements, underlying assumptions and interpersonal dynamics crucial for the efficient exchange of patient information (Galatzan et al., 2019; Galatzan & Carrington, 2022). Furthermore, it delves into the realm of human cognition, the intricacies of processing information from diverse sources and the examination of cognitive overload, its development and its consequences (Galatzan et al., 2019; Galatzan & Carrington, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most critical point for communication is the handover ( 22 , 23 ) that has to be structured to improve the safety by building a care setting in which information is encoded so that “the sender” and “the receiver” can understand whether the process has been correctly performed ( 21 , 24 ). It is therefore useful to implement “the closed loop communication” ( 25 ) to make all the caregivers able to verify the exact and complete communication of the patient’s clinical condition by a clear and shared language in terms of parameters and nomenclature understandable by all the caregivers involved in the patient care.…”
Section: The Patient Safety In Ebpt Of Critical Patientsmentioning
confidence: 99%
“…62 Townsend-Gervis et al 63 reported that hospital readmission dropped from 14.5% to 2.1% in a unit that employed IDR. After implementing daily bedside IDR, Clay-Williams et al 64 reported improved teamwork, communication, and understanding within and between clinical professions and between clinicians and patients. They did not find statistically significant differences in length of stay but did observe a drop in cost of stay.…”
Section: Interdisciplinary Rounding (Idr)mentioning
confidence: 99%